Applications of Polymeric Materials in Biomedical Engineering - Mukhtar, A. (Springer Nature, 2021)
The class of multipurpose materials having countless properties for various applications in particular based on their relationship between structure and property is known as polyurethanes (PUs). Particular attention was given to the adaption of different applications of PUs with its unique physical, mechanical, chemical, and biological characteristics. Increasing the potential and efficiency of materials based on PU may be accomplished by modifying the production process or utilizing state-of-the-art characterization techniques. Changes to raw materials and production procedures by suitable methods will easily yield PUs fit for different unique applications. Over the last decade, significant experiments have been performed on the usage of polymers such as medication delivery devices, implants, tissue engineering scaffolds, etc. The discovery of a better synthesis method for polymer systems based on biologically dependent macromolecules may be encouraged by this information. Â© 2021, The Author(s), under exclusive license to Springer Nature Switzerland AG.